The problem of the political self-identity in papers of Cyril and Methodius authors - M. P. Boyko (Granì, 2016)
The problems of the creation of the basic reasons of Ukrainian nation’s political identity in the context of cultural and political dimension have been revealed in the article. It has been found that Cyril and Methodians understood the reasons of political division, which had historical and spiritual background. It has been shown that members of Cyril and Methodiy’s company tried to determine the variations of directions in the development of national and political unity and to determine the Ukrainian national - cultural priorities. They argued that the Ukrainian mentality had been formed on the basis of the following dominant principles: respect to the family, esthetical love to their native land, rational and ethical attitude and respect to human life. It has been indicated, that Cyril and Methodians had proven the idea about the state of the national culture, which had transformed into the global culture through Russian culture, although Ukrainian and Russian culture had perceived differently the importance of global processes. Big attention has been paid to the fact that free Ukrainian people had the experience of struggling for the affirmation of present national character, they did not want to form unions that would destroy freedom. The achievements of Ukrainian national freedom have been described primarily in the implementation of the “freedom” of the individual. Statements of the human freedom being the need of self-expression inside the individual freedom by means of obtaining a sign of social freedom have been suggested. It can be provided when collectivism has no pressure on the will of the individual and cannot influence its intellectual potential. The emphasis has been referred to the fact that the psychology of self-defense is based on Ukrainian cultural achievements being the part of its national identity. The forms of language development, the construction of temples, traditional rituals of rural life have been developed. The “live” power laid in national and cultural achievements of Ukrainians as they borrowed the values from other cultures and adapted to their minds. This happened due to the fact that national culture was formed as a specific element of the current world culture and withstand the pressure of “great power.” It has been noted that Ukrainians contributed to the development of Russian culture, they dissolved this so-called Little Russian mentality in the Russian public sphere and popularized Ukrainian spirit. The impact of ideas of European Slavophiles Decembrists, Ukrainian philosophers to the attitudes of Cyril and Methodius has been reviewed. Theoretical and methodological basis to analyze the maturing political identity formed work of contemporary philosophers, political scientists, cultural studies, where they were identified and developed fundamental categories methodology regarding patterns of political thinking Ukrainian nation.